The oxylipins profile and their associations with embryo quality of women with polycystic ovary syndrome: a prospective cohort study - Ye Tian; Fang Li; Tuo Kuang; Xiangning Li; Xin Zhou; Xiaohong Bai (Gynecological Endocrinology)
This study was aim to investigate the oxylipins profile in the follicular fluid (FF) of women with PCOS and examine their associations with embryo quality.We conducted a targeted lipidomic study involving sixty-two cases of PCOS and age-matched controls (Cohort 1) via UHPLC–MS. Cohort 2 included sixty cases of PCOS and age-and-BMI-matched controls who were recruited for validation via targeted lipidomics. The associations between these oxylipins and baseline hormones as well as embryo quality in PCOS patients were analyzed.A total of 59 oxylipins were identified in the FF of PCOS patients. In the FF of PCOS patients in Cohort 1, the level of 16(17)-EpDPE, a product derived from docosahexaenoic acid (DHA), was greater than that in the control group, even after adjustment for age, BMI and multiple comparisons (p < 0.001, adjusted p = 0.032). An increased concentration of 16(17)-EpDPE in women with PCOS was further validated in Cohort 2 (p < 0.001, adjusted p = 0.044). In addition, compared with the control group, the PCOS group in Cohort 2 presented significantly lower levels of eicosapentaenoic acid (EPA)-derived oxylipins (18-HEPE), DHA-derived oxylipins (4-HDoHE, 16-HDoHE), linoleic acid(LA)-derived oxylipins (12,13-EpOME, 13-HODE and 9-oxoODE), and dihomo-gamma-linolenic acid(DGLA)-derived oxylipins (15-HETrE). Correlation analyses between oxylipin metabolites and clinical features revealed that 16(17)-EpDPE was negatively associated with the number of D3 good-quality embryos and positively associated the blood lymphocyte count. Three LA-derived oxylipins were associated with the serum AMH and leptin levels in the FF.Our study revealed distinct metabolic signatures in women with PCOS and identified 16(17)-EpDPE as a novel biomarker for PCOS and their D3 good-quality embryos count.